Slow Sodium: An Oral Slowly Released Sodium Chloride Preparation. Issue 5775 (11th September 1971) - Clarkson, E. M.; Curtis, J. R.; Jewkes, R. J.; Jones, B. E.; Luck, V. A.; de Wardener, H. E.; Phillips, N.
Abstract : The use of a slowly released oral preparation of sodium chloride is described. It was given to patients and athletes to treat or prevent acute and chronic sodium chloride deficiency. Gastrointestinal side effects were not encountered after the ingestion of up to 500 mEq in one day or 200 mEq in 10 minutes.